2012
DOI: 10.12693/aphyspola.122.606
|View full text |Cite
|
Sign up to set email alerts
|

Annealing Effects after Various Thermo-Mechanical Treatments on Microstructure and Mechanical Properties of Wrought Magnesium Alloy ZK60

Abstract: The magnesium alloy ZK60 received from Dead Sea Magnesium in direct-chill cast condition was extruded at T = 350• C using an extrusion ratio of ER = 12. The extruded bars were severely plastically deformed at 250• C by either equal channel angular pressing or swaging. While swaging led to similar grain renements as observed after equal channel angular pressing, yield stress and tensile strength values were by far superior in the swaged material. This result is explained by the unfavourable 45• texture componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In our study, the microstructure was severely rened by extrusion in the beginning. Similar behavior was found in the ZK60 alloy, where a bimodal microstructure with small grains of 12 µm was achieved by extrusion [9]. Subsequent swaging resulted only in the unication of the grain size distribution similar to this study.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the microstructure was severely rened by extrusion in the beginning. Similar behavior was found in the ZK60 alloy, where a bimodal microstructure with small grains of 12 µm was achieved by extrusion [9]. Subsequent swaging resulted only in the unication of the grain size distribution similar to this study.…”
Section: Resultssupporting
confidence: 86%
“…In the recent years, a positive eect of the grain renement on the corrosion resistance was shown that was achieved mainly by equal channel angular pressure (ECAP) [7,8]. It was shown that grain renement due to the RS could lead to comparable grain size as achieved by ECAP [9]. This technique is very interesting as it enables much faster throughput and lower operating costs than other severe plastic deformation methods.…”
Section: Introductionmentioning
confidence: 99%
“…By optimizing the processing conditions of RS (temperature, feeding velocity) one may attain even ner-grained microstructure than by direct or indirect extrusion [17]. Our earlier study indicated enhanced strength without substantial deterioration of ductility and enhanced fatigue properties in RS ZK60 alloy as compared to ECAP processed material [18].…”
mentioning
confidence: 91%
“…Oo et al [12] investigated RSW-treated magnesium alloy ZK60. They concluded that despite the achievement of coarser microstructure by RSW than by equal channel angular pressing (ECAP), the yield strength and the ultimate tensile strength of the swaged material were superior.…”
Section: Introductionmentioning
confidence: 99%